2017
DOI: 10.1159/000479280
|View full text |Cite
|
Sign up to set email alerts
|

Serum CA19-9 Response Is an Early Predictive Marker of Efficacy of Regorafenib in Refractory Metastatic Colorectal Cancer

Abstract: Purpose: Regorafenib improves survival in chemorefractory metastatic colorectal cancer (mCRC) patients. However, regorafenib induces various adverse events (AEs) that often impair patients' quality of life. Identification of early predictive markers of the efficacy is warranted. Methods: We retrospectively examined 146 consecutive mCRC patients who received regorafenib. Clinical parameters, including patient background, AEs, and changes in biochemical parameters until day 28, were evaluated to identify efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The association of CA19-9 with the efficacy of apatinib has not been reported but there is evidence in similar biomarker studies of other anti-angiogenic agents. Levels of or changes in CA19-9 have been reported to predict the efficacy of bevacizumab or bevacizumab-containing chemotherapy and regorafenib in mCRC in some previous studies [55][56][57] . We have suggested two possible reasons why CA19-9 rather than CEA was an early predictive factor in our study.…”
Section: Discussionmentioning
confidence: 97%
“…The association of CA19-9 with the efficacy of apatinib has not been reported but there is evidence in similar biomarker studies of other anti-angiogenic agents. Levels of or changes in CA19-9 have been reported to predict the efficacy of bevacizumab or bevacizumab-containing chemotherapy and regorafenib in mCRC in some previous studies [55][56][57] . We have suggested two possible reasons why CA19-9 rather than CEA was an early predictive factor in our study.…”
Section: Discussionmentioning
confidence: 97%
“…A retrospective study of 121 mCRC patients treated with regorafenib evaluated the role of serum biochemical parameters such as carcinoembryonic antigen and carbohydrate antigen 19-9 (CA 19-9) as predictive biomarkers. 52 In both univariate and multivariate analyses, early CA 19-9 decrease was identified as an independent predictive factor of response to regorafenib therapy. These results require further validation using external data sets prior to clinical use.…”
Section: Identification Of Biomarkersmentioning
confidence: 91%
“…Indeed, there is no predictive biomarker to allow the selection of patients most likely to benefit from regorafenib (11). However, Komori et al (15) reported that serum CA19-9 response was an early predictive marker of efficacy of regorafenib in mCRC.…”
Section: Discussionmentioning
confidence: 99%